A Clinical Perspective of Low Carbohydrate Ketogenic Diets: A Narrative Review - Sukkar, Samir Giuseppe; Muscaritoli, Maurizio (Frontiers in Nutrition, 2021)
Low carbohydrates diets (LCDs), which provide 20 to 120 g of carbohydrates per day, have long been used as therapeutic options in the treatment of severe obesity, type 2 diabetes mellitus and other morbid conditions, with good results in terms of weight loss and control of the main metabolic parameters, at least in the short and medium term. According to the caloric content and the macronutrient composition, we can classify LCDs in hypocaloric, normoproteic diets (such as the Very Low-Calorie Ketogenic Diet [VLCKD] or the protein-sparing modified fasting [PSMF]), hypocaloric, hyperproteic and hyperlipidic diets (e.g., Atkins, Paleo diets…) and normocaloric, normo-/hyperproteic diets (eucaloric KD), the latter mainly used in patients with brain tumors (gliomas) and refractory epilepsy. In addition to LCD diets, another interesting dietary approach which gained attention in the last few decades is fasting and its beneficial effects in terms of modulation of metabolic pathways, cellular processes and hormonal secretions. Due to the impossibility of using fasting regimens for long periods of time, several alternative strategies have been proposed that can mimic the effects, including calorie restriction, intermittent or alternating fasting, and the so-called fasting mimicking diets (FMDs). Recent preclinical studies have shown positive effects of FMDs in various experimental models of tumors, diabetes, Alzheimer Disease, and other morbid conditions, but to date, the scientific evidence in humans is limited to some opens studies and case reports. The purpose of our narrative review is to offer an overview of the characteristics of the main dietary regimens applied in the treatment of different clinical conditions as well as of the scientific evidence that justifies their use, focusing on low and zero-carb diets and on the different types of fasting.